Effect of Maternal Hemoglobin on Gestational Age of Newly Born Babies in Baqubah City - Sabah Mohsin Ali; Mohammad Abdul Qader Al_Chalabi; Falah Mkhaiber Mustafa (Diyala Journal of Medicine, 2019)
Background: Maternal hemoglobin during pregnancy is well established to be contributors to affect gestational age of newly born babies. Anemia is one of most prevalent nutritional deficiency problem afflicting pregnant women in both developed and developing country.